The influence of blockchain-based food traceability on retailer choice: The mediating role of trust. (November 2021) - Garaus, Marion; Treiblmaier, Horst
Abstract: In the last decades, numerous food scandals have attracted policy makers' interest and subsequently induced retailers to actively improve food safety. Blockchain technology allows consumers to track the flow of food products and reduce food fraud, such as counterfeiting, dilution, or adulteration. Using three experiments conducted with Austrian business students as well as an online convenience sample, we investigate how the traceability of food products impacts consumers' trust in the retailer and subsequently influences consumers' retailer choice. Our model further considers retailer familiarity and the disclosure of blockchain benefits as important moderators of the impact of blockchain-based traceability systems on trust in the retailer. The model was tested using ANOVA, ANCOVA, and Hayes' PROCESS models. In terms of fostering consumer trust, the findings show that retailers who are unfamiliar to consumers profit more from the use of blockchain technology than do better-known retailers. Moreover, informing consumers about specific blockchain benefits strengthens the positive effects of a blockchain-based traceability system. Highlights: A blockchain-based traceability system positively impacts retailer choice. This influence is mediated by trust in the retailer. Retailers unfamiliar to consumers profit more from the use of blockchain technology. Communicating specific blockchain benefits is most effective.